Attention Bias and Recognition of Sexual Images - Novák, Ondřej; Bártová, Klára; Vagenknecht, Václav; Klapilová, Kateřina (Frontiers in Psychology, 2020)
Attention to sexual stimuli is necessary for the development of sexual response, yet while there is some evidence of attention bias in favor of sexual stimuli, the direction and magnitude of the effect remain so far unknown. A high-powered sample of 113 participants was tested using the dot-probe task and picture recognition task to measure visuospatial attention to erotic images. Participants showed no attention bias in the dot-probe task (rB = 0.201, p = 0.064) but were significantly better at recognizing erotic rather than neutral or training pictures (d = 1.445 and 1.461, respectively, both p < 0.001). These results indicate that spatial attention bias to sexual pictures is small, negligible, eventually nonexistent, or else the dot-probe task is not a reliable tool to assess it. Results of the picture recognition task, on the other hand, show that sexual stimuli are prioritized in memory and this should be explored in detail in future research.